2019
DOI: 10.1088/1755-1315/316/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Value of Forest Ecosystem Natural Potential in the Areal Regional Richness Structure

Abstract: Value of forest ecosystems’ natural potential is examined as composition of forest resources (timber and non-timber forest products) as natural capital. Also, value is examined as composition of environment-forming and social functions of forest objects as part of ecological potential of forest areas. Regional (national) richness includes all natural resources, all tangible and intangible assets made by nature and humanity in this region. By calculation results, value of forest resources (natural capital of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Our research shows, for instance, that within the broad group of coniferous forests, the overall ES potential is the highest for forests with moderately fertile and moderately moist soils, and clearly lower in less fertile, dry, moist, and swamp forests. Similar relationships were also described in other world regions, e.g., in the Urals (included ES: timber supply, air protection, water protection, climate forming, and soil forming), regardless of whether the dominant coniferous species was pine or spruce (Lebedev et al, 2019). The existence of a similar relationship can also be concluded based on data from Sweden, where it was shown that the provision of many services is higher with greater tree species richness (Gamfeldt et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…Our research shows, for instance, that within the broad group of coniferous forests, the overall ES potential is the highest for forests with moderately fertile and moderately moist soils, and clearly lower in less fertile, dry, moist, and swamp forests. Similar relationships were also described in other world regions, e.g., in the Urals (included ES: timber supply, air protection, water protection, climate forming, and soil forming), regardless of whether the dominant coniferous species was pine or spruce (Lebedev et al, 2019). The existence of a similar relationship can also be concluded based on data from Sweden, where it was shown that the provision of many services is higher with greater tree species richness (Gamfeldt et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…-making payments for the use of the forest fund taxable; -prescriptive establishment of minimum rates of payment for wood that do not reflect either the forest rent or the standard costs of forest reproduction. Many scientists and authors see the following mechanism for distributing rental income [6,7,8,9,10]. The main value of forest resources can be expressed by discounting the present value of future rents.…”
Section: Results Study Discussion Suggestionsmentioning
confidence: 99%
“…For a full version of the assessment of biodiversity in woodlands, a comprehensive, complete assessment of forest land also requires the inclusion of costs for the study of the values of the environment-forming functions of forests [6,7].…”
Section: Results Study Discussion Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation